SOSIALISASI PENERAPAN DIGITAL MARKETING UNTUK MENINGKATKAN UMKM DI DESA TANJUNG ALAM (SEBAGAI UPAYA PENINGKATAN UMKM MASYARAKAT) - Dea Pratiwi, Intan; Amnah Qurniati (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
Public understanding of how to systematically maximize existing resources is still lacking. Many MSMEs market their products conventionally due to a lack of understanding of online marketing. This activity is expected to increase the adoption of digital marketing among MSMEs in the community. This activity is carried out by providing outreach on the importance of digital marketing for the sustainable development of MSMEs in the community. This outreach activity requires several stages: the first is planning the activity, the second is implementing the outreach activity, and the final stage is evaluating the activity. The outcome of this activity is that the community understands how to implement digital marketing to continuously improve MSMEs in Tanjung Alam Village, and the community now understands how to promote MSMEs online.